(untitled) (Agroindustria, Sociedad y Ambiente, 2021)
The present investigation studied the problem framed in 41% of quarterly incomplete orders for automotive parts that were not found at the time of assembling the orders, despite the fact that the inventory system indicated their existence. To solve the situation, the general objective was to "Design a plan for routine management in the warehouse of the automotive spare parts distributor Mayorvenca CA". It was developed through the PDCA cycle methodology applied to a population of 6 people and using as information gathering instruments: brainstorming, the affinity and cause-effect diagram, the 5W and 1H and the checklist between others. Once the plan was implemented, the following results were obtained: that, with respect to the total of incomplete orders, 85% was due to the lack of a precise location and the other 15% due to errors in the inventory system, both causes were reduced to 0%; Regarding the process indicators, the Time to Load the Order (TCP) took up to 40 minutes and the Time to Take the Order (TSP) took up to 2 days, both indicators reached their target value of 10 and 15 minutes respectively. Thus, it was concluded in the reduction of 0% of incomplete orders.